2010
DOI: 10.3109/14756360903169592
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthesis of α-methyl-γ-lactones and in vitro evaluation of their activity on protein farnesyltransferase

Abstract: The semisynthesis of xanthanolide derivatives is reported from xanthinin and 4-epi-isoxanthanol, two sesquiterpene lactones isolated from the crude chloroformic extract of the leaves of Xanthium macrocarpum DC. (Asteraceae) by liquid/liquid chromatography. In vitro evaluation of their protein farnesyltransferase (PFTase) inhibitory activity has been investigated. In contrast to other biological activities of xanthanolides, PFTase inhibition is not associated with the presence of the potentially toxic alpha-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Although the isolation of 11β, 13-dihydroxanthinosin ( 3 ) from Tithonia diversifolia has been reported 23 , our 1 H- and 13 C-NMR data did not correspond well with the reported data. The published 1 H- and 13 C-NMR data of 3 indicated that it can be obtained through the reduction of xanthatin; however, the stereochemistry at the C-11 position could not be confirmed 15 . Meanwhile, another study afforded 3 as a product of the cross metathesis of a xanthatin-intermediate and methyl vinyl ketone followed by 1,4- reduction, yielding 3 as the diastereomer of 11β,13-dihydro-tomentosin 16 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the isolation of 11β, 13-dihydroxanthinosin ( 3 ) from Tithonia diversifolia has been reported 23 , our 1 H- and 13 C-NMR data did not correspond well with the reported data. The published 1 H- and 13 C-NMR data of 3 indicated that it can be obtained through the reduction of xanthatin; however, the stereochemistry at the C-11 position could not be confirmed 15 . Meanwhile, another study afforded 3 as a product of the cross metathesis of a xanthatin-intermediate and methyl vinyl ketone followed by 1,4- reduction, yielding 3 as the diastereomer of 11β,13-dihydro-tomentosin 16 .…”
Section: Resultsmentioning
confidence: 95%
“…The isolated compounds were identified as xanthinosin ( 1 ) 4 , 11α, 13-dihydroxanthinin ( 2 ) 4 , 11β, 13-dihydroxanthinosin ( 3 ) 15,16 , 4α, 11α, 13-trihydroxanthuminol ( 4 ) 4 , desacetylxanthanol ( 5 ) 4 , lasidiol p -methoxybenzoate ( 6 ) 4 , 1, 5-dicaffeoylquinic acid ( 7 ) 17 , (-)loliolide ( 8 ) 18 , caffeic acid ( 9 ) 19 , protocatechuic acid ( 10 ) 20 , 4-hydroxybenzoic acid ( 11 ) 21 , and patuletin ( 12 ) 22 by comparing the obtained 1 H- and 13 C-NMR and ESI-MS data with that published in the literature (Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported the semisynthetic unseparable diastereomeric mixture at position C-4 and C-11. 20 The 1 H and 13 C NMR spectral data ( Table 2) and HMBC spectra led to the identification of three sp 3 methyl, four sp 3 methylene, five sp 3 methine, one sp 2 methine, one sp 2 quaternary carbon, and one carbonyl carbon atom in the compound 3. The difference NOE correlations between H-8, H-13, and H-14 showed that b-methyl substituted trans lactone ring fused with b-oriented 14-methyl group containing seven membered ring in compound 3 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Compounds 2 and 3 were first isolated from natural resources and compounds 1, 4, and 5 were known compounds. All (1)(2)(3)(4)(5) compounds showed potent TRAIL-resistance overcoming activity in TRAIL-resistant AGS cells at 8,20,20,16, and 16 lM respectively. Xanthinosin (1) also showed TRAIL-resistance overcoming activity in HeLa cells, DLD1 cells, DU145 cells, and MCF7 cells but compound 1 did not decrease viability in non-cancer HEK293 cells upto 8 lM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation